Management of Operational Assistance Funds (BOS) in State Madrasah Tsanawiyah 15 Jakarta - Dian Rosdiana; R. Luki Karunia; Edy Sutrisno (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study examines the management of Operational Assistance Funds (BOS) in State Madrasah Tsanawiyah 15 Jakarta, focusing on the allocation, utilization, and accountability of these funds. BOS plays a vital role in supporting the operational needs of educational institutions in Indonesia, particularly state madrasahs. This research employs a mixed-methods approach, combining quantitative analysis of financial data and qualitative investigation into administrative practices. The study finds that the allocation of BOS funds in State Madrasah Tsanawiyah 15 Jakarta aligns with government guidelines, with funds being distributed based on student enrollment and the institution's specific needs. However, challenges in fund utilization and accountability are identified. These include delays in disbursing funds, discrepancies in fund allocation, and the need for improved financial reporting mechanisms. These issues can impact the effectiveness of educational programs and infrastructure development. To enhance the management of BOS funds in this madrasah, the research recommends streamlining the fund disbursement process, enhancing transparency and accountability through better financial reporting, and promoting the efficient use of funds to improve the quality of education and facilities. Addressing these challenges is essential to ensuring that BOS funds effectively support the mission of State Madrasah Tsanawiyah 15 Jakarta in providing quality education to its students.